Analysis of Trace Element Concentrations of Some Lichens of Turkey - ASLAN†, ALI; APAYDIN‡, GÖKHAN; YAZICI*, KENAN; CENGIZ‡, ERHAN; AYLIKCI‡, VOLKAN; TIRASOGLU‡, ENGIN (Asian Journal of Chemistry, 2009)
In this study, concentrations of six different elements (Ca, K, Fe, Ba, Ti and Sr) were measured in twelve lichen species from two geographically different regions (Northern Anatolia: Provinces of Trabzon, Ordu, Artvin and Giresun and Eastern Anatolia: Erzurum province) in Turkey. An annular 55Fe and 241Am radioactive source was used for excitation of characteristic K X-rays using radioisotope excited energy dispersive X-ray fluorescence method of multiple standard addition. The incident beam and fluorescence X-rays emitted from the target were detected and analyzed with an Ultra-LEGe detector. Five of the six elements (Ca, K, Fe, Ba and Ti) are available in the twelve lichen species living in 12 different habitats. But, Sr is the only available element in some lichens living in some certain localities. Moreover, some lichens living in some localities contain very high concentrations (almost 5-10 folds) of Ti and Ba (for example: Ordu-Ünye Çinarsuyu, Erzurum-Kösk village for Ti, 0.384, 0.342 %, respectively and Trabzon-Maçka, Solma plateau for Ba and 0.306 %).